Histological evaluation of the cleaning effectiveness of two reciprocating single-file systems in severely curved root canals: Reciproc versus waveOne - de Souza Carvalho, Maira; Sponchiado Junior, Emílio Carlos; Bitencourt Garrido, Angela Delfina; Roberti Garcia, Lucas da Fonseca [UNESP]; Franco Marques, André Augusto (Thieme, 2015)
Objective: The aim of this study was to evaluate the cleaning effectiveness achieved with two reciprocating single-file systems in severely curved root canals: Reciproc and WaveOne. Materials and Methods: Twenty-five mesial roots of mandibular molars were randomly separated into two groups, according to the instrumentation system used. The negative control group consisted of five specimens that were not instrumented. The mesial canals (buccal and lingual) in Reciproc Group were instrumented with file R25 and the WaveOne group with the Primary file. The samples were submitted to histological processing and analyzed under a digital microscope. Results: The WaveOne group presented a larger amount of debris than the Reciproc Group, however, without statistically significant difference (P > 0.05). A larger amount of debris in the control group was observed, with statistically significant difference to Reciproc and WaveOne groups (P < 0.05). Conclusions: The two reciprocating single-file instrumentation systems presented similar effectiveness for root canal cleaning.
Keywords: Cleaning; Reciprocating motion; Reciprocating single-file system